Strategi Personal Branding Komposer Musik di Media Sosial (Studi Kasus Personal Branding Alffy Rev di Instagram) - Ratnasari, Dwinita (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Alffy Rev is a music composer who has a digital music character who collaborates with ethnic musics. Alffy Rev builds his personal brand through social media such as Instagram. This research was made to show a personal branding strategy made by Alffy Rev on his way up to now which is reviewed through Instagram social media. This process is summarized in the form of personal branding strategy theory which consists of eight laws : Specialization, Leadership, Personality, Distinctiveness, Visibility, Unity, Persistence, Goodwill. All of these laws form a character or identity of a person, and the most important thing is to be consistent in carrying them out. With the branding strategy in progress, Alffy Rev said that his brand name is a great asset which is still maintained its strength until now Personal branding is one of the marketing strategies which is very important to be pursued by a music composer. Personal branding is one of the marketing strategies which is very important to be pursued by a music composer. In general, the existence of music artists is more dominant to singers and musicians. Before the digital era, the image of a music composer was simply someone who made music and worked backstage. Not many people can appreciate the work of music composers because they are not well known or not widely publicized by the media. However, after the presence of social media, music composers began to appear who were arguably more dominant than the singers. The singer acts as a companion to the music composer or commonly referred to as featuring.